Towards the Ethics of a Green Future - Duewell, Marcus; Bos, Gerhard; van Steenbergen, Naomi (Routledge Studies in Sustainability, 2018)
What are our obligations towards future generations who stand to be harmed by the impact of today's environmental crises? This book explores ecological sustainability as a human rights issue and examines what our long-term responsibilities might be. This interdisciplinary collection of chapters provides a basis for understanding the debates on the provision of sustainability for future generations from a diverse set of theoretical standpoints. Covering a broad range of perspectives such as risk and uncertainty, legal implementation, representation, motivation and economics, Towards the Ethics of a Green Future sets out the key questions involved in this complex ethical issue. The contributors bring theoretical discussions to life through the use of case studies and real-world examples. The book also includes clear and tangible recommendations for policymakers on how to put the suggestions proposed within the book into practice. This book will be of great interest to all researchers and students concerned with issues of sustainability and human rights, as well as scholars of environmental politics, law and ethics more generally.